2007
DOI: 10.2217/14622416.8.9.1127
|View full text |Cite
|
Sign up to set email alerts
|

C-440T/T-331C Polymorphisms in the UGT1A9 Gene Affect the Pharmacokinetics of Mycophenolic Acid in Kidney Transplantation

Abstract: The study demonstrated a significant impact of C-440T/T-331C SNPs in the promoter region of the UGT1A9 gene on MPA pharmacokinetics in renal allograft recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 47 publications
2
70
2
Order By: Relevance
“…Several reports have found that the pharmacokinetics of MPA in humans is characterized by large inter-and intraindividual variability and that glucuronide activity from MPA may be involved in the between-individual variability (Kuypers et al, 2005;Baldelli et al, 2007). In the present study, we focused on the importance of the MMF bioactivation pathway to MPA as a factor other than the MPA glucuronidation pathway previously researched.…”
Section: Discussionmentioning
confidence: 95%
“…Several reports have found that the pharmacokinetics of MPA in humans is characterized by large inter-and intraindividual variability and that glucuronide activity from MPA may be involved in the between-individual variability (Kuypers et al, 2005;Baldelli et al, 2007). In the present study, we focused on the importance of the MMF bioactivation pathway to MPA as a factor other than the MPA glucuronidation pathway previously researched.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to these SNPs, Baldelli et al . [112] have also shown that −440 C>T and −331 T>C SNPs of the UGT1A9 promoter region were associated with an increased systemic exposure to MPA in renal transplant patients. Besides UGT1A9, the role of genetic polymorphisms in other UGTs on MPA pharmacokinetics is less clear.…”
Section: Genetic Polymorphismmentioning
confidence: 89%
“…Thus, edaravone has a high affinity toward UGT1A9 and may have the potential to inhibit the glucuronidation of UGT1A9 substrates. In addition, genetic polymorphisms of UGT1A9 have been implicated in the interindividual variation of mycophenolic acid metabolism (Kuypers et al, 2005;Baldelli et al, 2007;Sánchez-Fructuoso et al, 2009). The relationships between UGT1A9 polymorphisms and edaravone metabolism have never been mentioned before, but they should be paid more attention.…”
Section: Glucuronidation Of Edaravone By Hlm and Hkmmentioning
confidence: 99%